Draft Annual Plan 1987-88 Union Territory of Dadra and Nagar Haveli - Planning Commission (Planning Commission, 1987)
The Union Territory of Dadra and Nagar Haveli is situated near the Western coast of India nearly 200 Kms. north of Bombay. It is sandwitched between the Bulsar District of Gujarat and Thane District of Maharashtra. The coast of Arabian sea is about 30 Kms. and the N.H.8 is about 4 to 5 Kms. from the border of this Territory.
Planning Division Administration Dadra and Nagar Haveli